How to apply evidence-based principles in clinical dentistry - Durr-e-Sadaf (Journal of Multidisciplinary Healthcare, 2019)
Durr-e-Sadaf1,2 1Conservative Dentistry Department, College of Dentistry, Qassim University, Qassim, Saudi Arabia; 2Evidence Based Healthcare, Centre of Evidence Based Medicine, University of Oxford, Oxford, UK Abstract: The primary objective of evidence-based practice is to improve the quality of health care. It helps in making a clinical decision based on recent and advanced research and the best available evidence. Evidence-based dentistry is an integration of best available evidence with clinical expertise and patient’s needs and preferences. However, there are many barriers to apply evidence-based knowledge into practice. Information overflow, inability to select appropriate evidence, and critically appraising the evidence are the main challenges a practitioner may face. The focus of this review is defining a well-structured clinical question, key principles of literature search, type of search studies, and how to appraise an evidence. Furthermore, despite the availability of good evidence, patient’s needs and preferences are crucial factors in making clinical decision. Finally, the clinician’s experience and lack of motivation to change practice is another big challenge to evidence-based practice. This article discusses the six structured steps to apply evidence-based practice in dentistry with examples. Finally, this article will help practitioners to integrate their experience and skill with modern research evidence as well as to educate their patients to reach a final clinical decision. Keywords: evidence-based dentistry, decision making, PICO, systematic